2008
DOI: 10.1021/pr800086t
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Gender and Caloric Restriction on Liver Proteomic Expression Profile

Abstract: We analyzed the combined effect of gender and CR on protein expression profile in liver. We identified 27 differentially expressed proteins involved in several cellular functions such as substrate metabolism, antioxidant systems, stress response, iron homeostasis and cardiovascular protection. This study reveals new cellular pathways liable to be similarly regulated in females and calorie restricted rats and which could be related with the greater longevity in these animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 77 publications
0
10
0
1
Order By: Relevance
“…It is thus not surprising that invertebrate data (Drosophila) suggest that age-related iron accumulation is proportional to the rate of aging (Massie et al, 1985) and inhibition of iron absorption prolongs lifespan (Massie et al, 1993). Similarly, human gender differences in longevity have been proposed to relate to reproduction-related iron losses in women (Sullivan, 1989) and life-extending effects of calorie restriction have been associated with reduced dietary iron uptake and lowered iron deposits in tissue (Cook and Yu, 1998;Kastman et al, 2010;Valle et al, 2008;Xu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus not surprising that invertebrate data (Drosophila) suggest that age-related iron accumulation is proportional to the rate of aging (Massie et al, 1985) and inhibition of iron absorption prolongs lifespan (Massie et al, 1993). Similarly, human gender differences in longevity have been proposed to relate to reproduction-related iron losses in women (Sullivan, 1989) and life-extending effects of calorie restriction have been associated with reduced dietary iron uptake and lowered iron deposits in tissue (Cook and Yu, 1998;Kastman et al, 2010;Valle et al, 2008;Xu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The overall metabolism of fuel molecules displays sex differences, and in this context many hepatic proteins are expressed in a sexually dimorphic fashion (13,17,39). With relevance to hepatic glycerol metabolism, the expression of AQP9 protein is ϳ20% higher in male than in female rats in the postprandial state (26).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that glycolytic enzymes were less abundant in females in non-exercised murine skeletal muscle. Valle and colleagues [27] analyzed the combined effect of gender and caloric restriction on the protein expression profile in rat liver, and identified 31 sexually dimorphic (15 femaleand 16 male-dominant) proteins. However, differentially expressed proteins were interpreted in relation to longevity rather than obesity.…”
Section: Introductionmentioning
confidence: 99%